Prevalência de Ehrlichia canis pela técnica de nested-PCR e correlação com a presença de mórula e trombocitopenia em cães de Alegre-ES - Sales, Mara Rúbia Rocha Pereira (2012)
The aim of this study was determined by nested-PCR the presence of Ehrlichia canis in dogs located in the municipality of Alegre-ES and evaluate its correlation with morulae and thrombocytopenia. For this purpose blood samples were collected from 85 dogs, regardless of race, age, sex or health status. With these, slides were obtained for the detection of morulae, thrombocytopenia, and execution of nested-PCR technique. We verified a prevalence of 1.17% to investigated the presence of morulae, 5.6% when using the technique of nested-PCR, and was verified that 17.64% of the CBCs were thrombocytopenia. However, only 40% of positive samples by nested-PCR showed thrombocytopenia. The results presented in this study demonstrate that the introduction of molecular diagnostic techniques such as nested-PCR is an important method to aid in the early diagnosis of diseases